Phytochemistry of Calophyllum inophyllum L. and Calophyllum teysmannii Miq. and their biological activities - Lee, Kar Wei (2017)
The genus Calophyllum is consisted of 180-200 species of evergreen trees which are widely distributed in Asia and Africa. This genus is popularly known for their bioactive compounds such as terpenoids, xanthones and coumarins. The need of new drugs are on the rise due to the discovery of various new diseases. Besides, the development of drug resistant diseases also makes drug discovery research significant. Hence, natural products research is important as they provide new templates in the field of drug discovery. Detailed studies were carried out chemically and biologically on the stem bark of two selected plants species, Calophyllum inophyllum and Calophyllum teysmannii. A total of two terpenoid compounds and five xanthones were isolated from the n-hexane and chloroform crude extracts of Calophyllum inophyllum respectively. The terpenoids are friedelin (82) and stigmasterol (83) whereas the xanthones are caloxanthone A (23), caloxanthone B (24),caloxanthone C (43), pyranojacareubin (6) and macluraxanthone (5). On the other hand, a total of two xanthones were isolated from the n-hexane and methanol crude extracts of Calophyllum teysmannii correspondingly namely ananixanthone (29) and β-mangostin (84). The structures of the acquired compounds were elucidated by analyzing the spectroscopic data such as 1D NMR, 2D NMR, IR, and MS. Structural modifications on the parent compound ananixanthone (29) afforded four other new synthesized xanthone derivatives namely ananixanthone monoacetate (85), ananixanthone diacetate (86), 5-methoxyananixanthone (87), and 5-O-benzylananixanthone (88). Their structures were concluded through comparison with the parent compound’s NMR spectra. The crude extracts of both the plants were subjected to toxicity test against LPS stimulated RAW264.7 cells. The results indicated that only chloroform crude extract of Calophyllum inophyllum exhibited a promising result with an IC50 value of 14.81±0.0417 μg/mL. However, the rest of the crude extracts showed weak or no bioactivities. Determination of the antioxidant activities through DPPH scavenging assay indicated that the methanol crude extract of Calophyllum teysmannii exhibited the most significant antioxidant properties with the EC50 value of 33.06±0.36 μg/mL followed by moderate activities by the methanol crude extract of Calophyllum inophyllum. The remaining crude extracts showed weak or no activities. Besides, antimicrobial assay via disc diffusion method was carried out against seven different microbe strains. The n-hexane and chloroform crude extract of Calophyllum inophyllum showed strong inhibition against Staphylococcus epidermidis S273 and moderate inhibition against Bacillus Subtillis B145. The rest of the crude extracts showed weak or no inhibition against the microbes. Total Phenolic Content (TPC) of the crude extracts via the Folin-Ciocalteu method showed that the most polar crude extracts, the methanol crude extracts of both plants had the highest TPC value with 138.56 and 204.93 μg of gallic acid/mg of crude extracts individually. Lastly, cytotoxicity screening via MTT assay of ananixanthone (29) and four of its modified derivatives against three cancer cell lines, SNU-1, LS-174T and K562 resulted in ananixanthone (29) showing the greatest activities against SNU-1 and K562 cell lines with the IC50 values of 8.97±0.11 μg/mL and 2.96±0.06 μg/mL respectively. On the other hand, 5-methoxyananixanthone (87) indicated greater cytotoxic activity than its parent compound against LS-174T cell line with the IC50 value of 5.76±1.07 μg/mL.